Teacher Self-Awareness and Digitalization Strategies for Accreditation Quality Improvement in Educational Institutions - Yuwono Hardi; Siti Atwano Pisriwati; Deny Hadi Siswanto; Kintoko (Pustaka Bangsa Indonesia, 2026)
This study aims to analyze the accreditation preparation process at SMA Muhammadiyah Mlati, emphasizing teachers' self-awareness in understanding their emotions and professional roles. The research employs a qualitative approach with a case study design, allowing for an in-depth exploration of the experiences, perceptions, and collaborative practices of the school community. Data were collected through semi-structured interviews, direct observation, and documentary studies, then analyzed using the Miles and Huberman interactive model. The results indicate that the formation of an IASP-based Ad-Hoc team successfully enhanced task clarity and collective accountability. Furthermore, the digitalization of documents via cloud-based platforms improved efficiency, transparency, and data accessibility. Improvements in infrastructure also created a more conducive and representative learning environment. Additionally, strengthening the literacy culture and Muhammadiyah values proved effective in shaping students' character holistically. These findings underscore that accreditation preparation is not merely an administrative requirement but a comprehensive strategy for school quality improvement. Consequently, sustainability in digital system management, facility development, and the enhancement of teacher competence and self-awareness are essential to support long-term educational quality.